Predicting E-Banking Adoption : An Evaluation of Perceptions and Behavioural Intentions of Small and Medium Enterprises in Karnataka - Basri, Savitha; Shetty, Dhiraj (Indian Journal of Finance, 2018)
The Indian government supports small and medium enterprises in adopting and using e-banking services as a part of its ’Digital India’ campaign. Few studies have focused on the adoption of electronic banking by SMEs in India. Hence, it is imperative to understand the perception of SMEs to adopt e-banking services. The purpose of this paper was to empirically study the direction of relationships between perceived ease of use, perceived usefulness, perceived convenience, perceived self-efficacy, trust, perceived risk, government support, and intention to adopt online banking. A cross-sectional descriptive survey was carried out to gather quantitative data from 132 SMEs in Karnataka. The data were analyzed using the PLS method of structural equation modeling. The results showed that perceived usefulness, perceived risk, and perceived ease of use determined e-banking adoption. Trust was positively related to perceived risk of e-banking transactions. We found that perceived self-efficacy affected perceived ease of use that, in turn, determined perceived usefulness. Hence, the banks should provide training programmers to improve self-efficacy and allocate more resources to create an easy-to-use system and adopt risk reduction measures that inhibit identity theft and fraudulent activities over the Internet to foster trust among prospective SMEs. Unlike existing studies, our model included additional variables namely trust, perceived risk, perceived self-efficacy, and government support. This model could be applied to SMEs in other developing countries that are in the initial phases of adoption of online banking.